ANALISIS VARIABEL YANG MEMENGARUHI PEMILIHAN PRODUK TABUNGAN BRITAMA PERIODE TAHUN 2023 - Wimardu, Dessylla Duarthe; Susilo (Contemporary Studies in Economic, Finance and Banking, 2023)
The purpose of this study was to determine the effect of initial deposit variables, monthly administration fees, labor force perceptions of their work, income, and promotions on prospective customers' decisions in choosing BritAma savings products compared to other savings products at PT. BRI (Persero), Tbk Kepanjen Branch Office and find out what factors have the most dominant influence on the decision. The author uses the Logistic Regression method or Logistics Model Analysis (LOGIT) to analyze qualitative data that reflects the choice between two alternatives. The results show that the initial deposit and income variables have a positive and significant effect, while the monthly administration fee variable has a negative and significant effect on customer decisions. Meanwhile, the labor force's perception of their work and promotions does not have a significant effect on customer decisions. The results of this study can be used as a benchmark for banking, especially PT. BRI (Persero), Tbk to improve its work efficiency in order to gain the trust of the public to save their funds in the bank.